HBCU Trains Communities of Color - Plummer, Yolandra (Advances in Social Sciences Research Journal, 2020)
In June 2020, the University of the District of Columbia began a dual virtual skills certificate program in response to the COVID-19 pandemic. The historically black college and university’s (HBCU) introductory program prepared individuals for careers as Contact Tracers and Community Health Workers. A sample of 55 students participated in the pilot program to learn how to investigate the spread of the COVID-19 virus. The program targeted District residents who received Temporary Assistance for Needy Families (TANF) benefits. The TANF program provided work readiness training to low-income families to enable them to move from public assistance to self-sufficiency. Program participants earned a dual certificate in Contact Tracing and Community Health Worker after completing the 20-hour program. The UDC work readiness program created a career pathway in healthcare which combines education, training, credentialing. The program includes support services to assist individuals with advancing in a high-demand occupation while earning a living wage. The demand for contact training demonstrates that HBCUs are a viable option to engage communities of colors to reduce the transmission of the COVID-19 virus.